Opportunistic forwarding for user-provided networks. Issue 6 (2nd November 2018) - Koutsogiannis, Efthymios; Mamatas, Lefteris; Tsaoussidis, Vassilis
Abstract: We study opportunistic forwarding in a community-based networking paradigm where mobile users and shared access points (SAPs) collectively provide Internet access to users (mobile or not), including those in areas where other connectivity options are not available. Our approach is based on an efficient interoperation of two challenging network types: the opportunistic and the user-provided networks (UPNs). This requires a re-evaluation of the existing assumptions regarding inter-contact patterns and their alignment to this hybrid environment. We confirm our arguments with numerical results from a stochastic model as well as experimental scenarios with realistic parameters using the ONE simulator. Our experiments are based on a reference routing algorithm we designed and implemented that extends the spray 'n focus protocol and exhibits the following characteristics: (i) is oriented to this integrated environment; (ii) employs delay-tolerant networking (DTN) technologies along with contact prediction; and (iii) is independent of the deployed UPN approach. According our results, the proposed methodological approach achieves lower communication overhead, latency and storage requirements compared to representative opportunistic routing algorithms. Graphical Abstract: Example of opportunistic forwarding for user-provided networks.